(untitled) - Flynn, Pat (San Diego, 2016)
This is the book I wish I'd read when I began my entrepreneurial journey. Its simple, practical, real-world advice would have saved me tons of time, money, and grief on the road to success. It's now my #1 recommendation for anyone who wants to launch a new product or business.
Keywords: Doanh nghiệp mới,New business enterprises